Virtual ileostomy - V. V. Darvin; S. V. Polozov; E. A. Krasnov; I. M. Karimov (Вестник хирургии имени И.И. Грекова)
The formation of low colorectal and coloanal anastomoses after low anterior and abdominal-anal resection of the rectum has always been a significant problem in surgery. A loop protective ileostomy can reduce the consequences of anastomotic leakage, which reaches 23 %, and in some cases avoid repeated emergency surgery. However, ileostomy also has negative consequences, such as the need for repeated surgery to eliminate the ileostomy, parastomal complications, large stoma losses, and low quality of life. A virtual ileostomy or “ghost ileostomy” has been proposed to avoid the unnecessary creation of the loop ileostomy. The article presents literature data on the use of virtual ileostomy for resection interventions on the rectum with the formation of a low colorectal anastomosis. According to most authors, the virtual ileostomy technique allows not only to avoid the unnecessary formation of the loop ileostomy, but also in the anastomotic leakage, it ensures the urgent application of the loop ileostomy in minimally invasive manner, without relaparotomy.